Macroprocess 09 Management of Human Capital - Organizational Design Division (Harold Zumbado Campos, 2020)
The Macroprocess 9 Human Capital Management aims to " Ensure the attraction, development and retention of the Institute's Human Capital to ensure the achievement of its objectives, promoting participative leadership to foster collaborative work and maintain a harmonic, respectful and efficient environment".